Epistemological and aesthetic implications of the scientific image for Visual Culture - Domínguez Muñino, Javier (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The current theoretical and educational models that concern the Visual Studies, subscribe a Visual Culture posed from the transversality; images go through different contexts, and perform different functions where aesthetic and epistemological regimes are debated. An example located in this framework is digital micrography: a visual corpus identified with technically produced images, highly artifact-mediated images, and read as knowledge devices. In this sense, the proposal is aligned with the so-called ACT (Arte, Ciencia, Tecnología) to make converge the different sensitive and epistemological channels; and it to describe a visual metaphorical process by which to translate abstract models into graphic codes that paradoxically generate emancipated images. Micrography, either as an encrypted sign or with visual unit, rethinks boundaries and categories in the academic field; as well as it opens a new path in visual artistic practice.
Keywords: visual culture; epistemology; aesthetic; micrograph; iconicity